The Effects of Chronic Nitrate Supplementation and the Use of Strong and Weak Antibacterial Agents on Plasma Nitrite Concentration and Exercise Blood Pressure - McDonagh, S. T. J.; Wylie, L. J.; Winyard, P. G.; Vanhatalo, A.; Jones, A. M. (International Journal of Sports Medicine, 2015)
Chlorhexidine-containing mouthwash (STRONG), which disturbs oral microflora, has been shown to diminish the rise in plasma nitrite concentration ([NO2−]) and attenuate the reduction in resting blood pressure (BP) typically seen after acute nitrate (NO3−) ingestion. We aimed to determine whether STRONG and weaker antiseptic agents attenuate the physiological effects of chronic NO3− supplementation using beetroot juice (BR). 12 healthy volunteers mouth-rinsed with STRONG, non-chlorhexidine mouthwash (WEAK) and deionised water (CON) 3 times a day, and ingested 70 mL BR (6.2 mmol NO3−), twice a day, for 6 days. BP (at rest and during 10 min of treadmill walking) and plasma and salivary [NO3−] and [NO2−] were measured prior to and on day 6 of supplementation. The change in salivary [NO3−] 4 h post final ingestion was higher (P<0.05) in STRONG (8.7±3.0 mM) compared to CON (6.3±0.9 mM) and WEAK (6.0±3.0 mM). In addition, the rise in plasma [NO2−] at 2 h was lower in STRONG compared with WEAK (by 89±112 nM) and CON (by 200±174 nM) and in WEAK compared with CON (all P<0.05). Changes in resting BP were not different between conditions (P>0.05). However, during treadmill walking, the increase in systolic and mean arterial BP was higher 4 h after the final nitrate bolus in STRONG compared with CON (P<0.05) but not WEAK. The results indicate that both strong and weak antibacterial agents suppress the rise in plasma [NO2−] observed following the consumption of a high NO3− diet and the former can influence the BP response during low-intensity exercise.
Keywords: beetroot juice; nitrate; antibacterial mouthwash; blood pressure; nitric oxide; exercise